"Гражданское общество" на примере Норвегии и его теоретическое наложение на украинские реалии - Гаряева, Анна Михайловна; Муренко, Елена Леонидовна (НТУ "ХПИ", 2013)
A brief analysis of the concept of civil society as such, as an example of one of the most developed European countries of Norway considers the effects generated by the freedom and political activists in the civil society of Norway, in particular terrorist attack by Anders Behring Breivik, carried ratio of the civil society of Norway and Ukraine, on the basis of what makes a brief conclusions on possible measures to address the problem in the Ukrainian society.
Keywords: Брейвик Андерс Беринг; ксенофобия; сегрегация; радикализм; теракт